Applications of wide-ranging PIV measurements for various turbulent statistics in artificial atmospheric turbulent flow in a wind tunnel. (November 2022) - Ikegaya, N.; Kikumoto, H.; Sasaki, K.; Yamada, S.; Matsui, M.
Abstract: Particle image velocimetry (PIV) is currently the only method which can experimentally quantify the spatial distributions of velocity with high sampling frequencies without causing intrusions into the airflow of the measuring devices. To extend the use of PIV systems for determining the distributions of velocity for wind environmental and engineering purposes, this study showed various applications of wide-ranging PIV systems for an artificially created turbulent flow at the wind-tunnel scale. Various turbulent statistics, which are commonly employed for evaluating the wind structures and environments, were compared among three conditions of the measurement areas covered by PIV systems and a hot-wire anemometry (HWA). The largest measurement covering 500 × 500 mm 2 can capture the turbulent motions extending to 40% of the entire boundary layer. In addition, the discrepancies on two-length scales could be discussed using spatial and temporal correlation functions owing to the wide-ranging PIV. Moreover, the limitations of the wide-ranging PIV systems were clarified. While the turbulent statistics compared among three PIV conditions and HWA demonstrated adequate agreement, the PIV with the largest measurement area failed to capture the small-scale turbulent structures due to the coarse grid resolutions. Moreover, the measurement resolutions of PIV systems demonstrated sensitivity in determining the spectrum and probability density functions, whereas a wide-ranging PIV system can cover wide-ranging measurement areas. Highlights: Applications of wide-ranging PIVs for turbulent flow at the wind-tunnel scale. Turbulent motions covering 40% of entire boundary layer captured over 500 × 500 mm 2 . Elucidated the limitations of the wide-ranging PIVs. Sensitivity in determining the spectrum and probability density functions by PIVs. Wide-ranging PIVs reduce the spatial resolutions of each measurement point.